MAKNA SIMBOLIK SAWAH DI MASYARAKAT PEDESAAN TINJAUAN KOMUNIKASI LINGKUNGAN PADA MASYARAKAT SEMENDE DARAT TENGAH KABUPATEN MUARA ENIM-SUMATERA SELATAN - Yenrizal, Agus Rahmat, Atwar Bajari, dan Johan Iskandar (Universitas Gadjah Mada, 2015)
Rice fields are an integral part in the life of rural communities, especially in the public of SemendeDarat Tengah, Muara Enim, South Sumatra. Rice fields are considered as part of the socio-culturaland economic of society. All of this is part of the communication process conducted by the publicenvironment, particularly the ability to understand the phenomenon of the local environment and thengive the meaning to the phenomenon. This is the focus of this study, environmental communicationprocess of society by looking paddy fields as a major agricultural. Through communication ethnoecologyapproach, this research shown that the people has made the construction process of the rice fields, whichare then considered to have a special meaning, ie the meaning of prosperous, the meaning of power,and the meaning of identity. All of not happen by itself, but a process of community communicationto understand their natural environment, in particular the existence of paddy. There are a symbolicconstruction mechanism which lasts from various groups in society.